Clinical Profile and Cardiovascular Disease among Chronic Obstructive Pulmonary Disease Patients - Bam, Niraj; Das, Satish Kumar; Shrestha, Bibek; Shrestha, Surya Jyoti (Nepal Journal of Health Sciences, 2025)
Introduction: Chronic Obstructive Pulmonary Disease is a major cause of morbidity and mortality worldwide, with systemic manifestations beyond the lungs. Cardiovascular disease is one of the most significant comorbidities, yet its prevalence among Chronic Obstructive Pulmonary Disease patients in low-resource settings like Nepal is underexplored.Objective: To assess the clinical profile of Chronic Obstructive Pulmonary Disease patients and determine the prevalence of cardiovascular comorbidities among those attending a tertiary care center in Nepal.Methods: This prospective cross-sectional study was conducted at Tribhuvan University Teaching Hospital, Kathmandu. Seventy adult patients with spirometry confirmed Chronic Obstructive Pulmonary Disease, recruited from inpatient and outpatient services, were enrolled. Patients with pre-existing hypertension, diabetes, or major cardiovascular conditions were excluded. Demographic data, smoking history, exposure risks, symptoms, and spirometry were recorded.Results: The mean age of participants was predominantly above 65 years, with females (61.4%) outnumbering males. Most patients were rural residents (68.6%), with 70% reporting smoking exposure. Symptomatically, half presented with dyspnea, cough, and sputum production, and 48.6% reported grade 4 dyspnea on the Modified medical research council dyspnea scale. Based on the Global Initiative for Chronic Obstructive Lung Disease classification, 57.1% of patients were in group D, indicating high symptom burden and exacerbation risk. Cardiovascular disease was documented in 11.4% of patients.Conclusions: This study demonstrates that cardiovascular disease is a notable comorbidity among chronic obstructive pulmonary disease patients in Nepal, even after excluding common confounders such as hypertension and diabetes. Most patients were elderly, female, and from rural areas with significant smoking exposure.